The Effects of Compaction Methods on Tensile Strength of Foamed Bitumen Mixture - Huan, Yue; Jitsangiam, Peerapong; Nikraz, Hamid; Siripun, Komsun (The Australian Geomechanical Society and New Zealand Geotechnical Society, 2012)
Currently, the introduction of the gyratory compactor replicating the kneading action of the field compaction raises a though that the conventional 75 blows of Marshall compaction effort would be insufficient to simulate field compaction of the foamed bitumen stabilisation material. Furthermore, the strong laboratory specification of a particular compaction method for the foamed bitumen mixture has not yet been established, therefore the future study in the compaction of the foamed bitumen mixture is needed. This laboratory based study aims to verify the reliable compaction effort for the foamed bitumen mixture. In this study, virgin materials treated with different foamed bitumen contents were compacted by Marshall Compactor and Gyratory Compactor at various blows/cycles, respectively. Upon completion of compaction and curing, density, indirect tensile strength and indirect tensile resilient modulus were performed to determine the suitable compaction technique for such materials. It is expected that the compaction effort achieved the highest density and tensile strength would be selected to compare with field compaction further.